2018
DOI: 10.3889/oamjms.2018.451
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study Examining the Correlation between Nocturnal Melatonin Level and Sleep Quality in Patients Admitted To the Cardiac Care Unit

Abstract: BACKGROUND:Quality of sleep, as a basic need, is an important factor for surviving patients in hospitals. Many factors may contribute to disturbing patients sleep, such as continuous ambient light, is required for healthcare providers to monitor patients. Ambient light can influence patients’ quality of sleep due to melatonin secretion.AIM:Study aimed to determine the correlation between nocturnal melatonin levels and sleep quality in patients admitted to the Cardiac Care Units (CCU).MATERIAL AND METHODS:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In this review, it is intuitive to think that specific measures to protect and stimulate the pineal gland with cycled lighting regulation in the ICU are capable of causing an increase in the endogenous production of this sleep‐regulating hormone, and in fact, three studies 17,21,23 measured this outcome, but none of them showed a statistical difference in urinary or plasma melatonin levels between intervention and control groups, which is intriguing and suggests that factors beyond cycled lighting may be related to melatonin production rhythm and intensity in critically ill patients 33,34 . However, in the study by Arık et al, 17 urinary melatonin levels were significantly higher after the first night of intervention in the experimental group compared with the baseline (pre‐intervention).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, it is intuitive to think that specific measures to protect and stimulate the pineal gland with cycled lighting regulation in the ICU are capable of causing an increase in the endogenous production of this sleep‐regulating hormone, and in fact, three studies 17,21,23 measured this outcome, but none of them showed a statistical difference in urinary or plasma melatonin levels between intervention and control groups, which is intriguing and suggests that factors beyond cycled lighting may be related to melatonin production rhythm and intensity in critically ill patients 33,34 . However, in the study by Arık et al, 17 urinary melatonin levels were significantly higher after the first night of intervention in the experimental group compared with the baseline (pre‐intervention).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital admission is another factor, which can increase the risk of sleep disturbances [9]. Accordingly, patients admitted to coronary care unit (CCU) are reported to have a poor quality of sleep, because of the underlying cardiac condition, effect of medications, hospital conditions, and stress and anxiety that they experience [10][11]. Considering that poor sleep quality is stressful, it can stimulate the release of epinephrine and norepinephrine, which consequently can be associated with tachycardia, tachypnea, increased myocardial oxygen requirements, and eventually leads to severe ischemia and MI [12].…”
Section: Introductionmentioning
confidence: 99%